Financial development, credit rationing and the distribution of income: South Africa 1913-2008 - Dos Santos, Claudia (School of Economics, 2014)
This paper provides a theoretical examination of the impact of financial development and credit constraints on earnings inequality in the country between 1923 and 2008. The time-span is particularly interesting, as it includes three distinct political regimes: colonialism, apartheid and democracy.